Incidence of paediatric pneumococcal meningitis and emergence of new serotypes: a time-series analysis of a 16-year French national survey. Issue 9 (September 2018) - ; Adam, Marie Noelle; Agha-Mir, Ilhem; Akitani, Sylvia; Amara, Marlène; Arlet, Guillaume; Asensio, Valérie; Autret, Fanny; Baleine, Julien; Barnaud, Guilaine; Barrans, Alain; Barsotti, Katia; et al.
Summary: Background: Successive implementation of seven-valent then 13-valent pneumococcal conjugate vaccines (PCVs) led to a marked decrease in pneumococcal disease burden, including pneumococcal meningitis. We assessed the long-term effect of implementation of PCVs on incidence of pneumococcal meningitis in children in France over a 16-year period. Methods: We did a quasi-experimental, population-based interrupted time-series analysis with a nationwide prospective survey over 16 years in France, recruiting children aged younger than 15 years from 227 paediatric wards from January, 2001, to December, 2016. The main outcome by the time-series model was the estimated incidence of pneumococcal meningitis per 100 000 children (of a population of 12·6 million children in 2017) before and after PCV7 and PCV13 implementation. The time-series model was based on segmented regression with autoregressive error. Findings: We enrolled 1778 children with pneumococcal meningitis. PCV13 implementation led to a significant reduction in monthly incidence of pneumococcal meningitis from 0·12 per 100 000 children before PCV13 to a nadir of 0·07 in December, 2014 (−38%, 95% CI −56·1 to −20·4; p<0·0001). A sharp increase occurred during 2015 and 2016, (+2·3% per month, incidence of 0·13 per 100 000 children at the end of the study period, p=0·0002), mainly related to an increase of serotype 24F, which was frequently penicillin resistant. Interpretation: The early effect of PCV13 implementation greatly reduced the incidence of pneumococcal meningitis in children less than 15 years old. However, a sharp rebound in incidence linked to the emergence of serotype 24F compromised the long-term PCV efficacy. If confirmed in future studies and in other countries, pneumococcal meningitis incidence rebound and 24F emergence should be considered when developing next-generation PCVs. Funding: The French Pediatric Infectious Diseases Group, Association Clinique et Thérapeutique Infantile du Val de Marne, Pfizer, and for the National Reference Centre for Pneumococci, the French National Health Agency.